Apollo Mission Control The Making of a National Historic Landmark - von Ehrenfried, Manfred "Dutch" (Space Exploration, 2018)
This book describes the history of this now iconic room which represents America's space program during the Gemini, Apollo, Skylab, Apollo-Soyuz and early Space Shuttle eras. It is now a National Historic Landmark and is being restored to a level which represents the day the flight control teams walked out after the last lunar landing missions. The book is dedicated to the estimated 3,000 men and women who supported the flights and tells the story from their perspective. It describes the rooms of people supporting this control center; those rooms of engineers, analysts and scientists most people never knew about. Some called it a "shrine" and some called it a "cathedral." Now it will be restored to its former glory and soon thousands will be able to view the place where America flew to the moon. .